Gaetano Salvemini’s exile in Great Britain and the construction of a transnational anti-fascist network (1925-1934) - Gussoni, A (2019)
Gaetano Salvemini was one of the most prominent intellectuals forced into exile during the Fascist period. The critical bibliography on Salvemini’s biography and intellectual production is already substantial, but the period of his European exile (1925- 1934) has remained largely unexplored. In-depth research carried out on archival sources in Britain, Italy, and the USA has allowed me to reappraise the importance of this period. Between 1925 and 1934, Salvemini benefitted from the support of a transnational network which had its headquarters in Britain. The network shared Salvemini’s anti-Fascist views and helped him to disseminate his work as a counterbalance to the propaganda machine of the Fascist regime.